Incidence and characteristics of antituberculosis drug-induced hepatotoxicity in children: a preliminary study - Bina Akura; Hanifah Oswari; Bambang Supriyatno; Najib Advani (Indonesian Pediatric Society, 2009)
Background Antituberculosis drugs show good efficacy but have adverse effects including hepatotoxicity.Objective To find the incidence and characteristics of antituberculosis hepatotoxicity in children during the first 2 weeks of therapy.Methods A cohort study was performed in Cipto Mangunkusumo, Persahabatan, and Tangerang Hospitals from August 2008 toMarch 2009. The diagnosis of tuberculosis (TB) based on TB scoring system. Laboratory tests were performed including transaminase enzymes, bilirubin, y-GT, albumin, ureum, and creatinine before and after 2 weeks of treatment. Patients were monitored during the first 2 weeks of therapy. Informed consent obtained from the parents.Results Six of 81 subjects had hepatotoxicity reaction. Most of the patients were 1 to 5 years old (65%) and well nourished (50%). Extrapulmonary tuberculosis found in 67% of cases. Thirty-three percents of patients received four agents. Thirty-three percents of cases received 4 agents combined with other hepatotoxic drugs. Six subjects had hepatotoxicity (1 hepatitis, 2 mixed case, and 3 asymptomatic). Two of 50 children (4%) with pulmonary TB and 4 out of 31 ( 13%) children with extrapulmonary TB had hepatotoxicity reaction. Antituberculosis drug doses were similar between the hepatotoxicity group and control.Conclusions Incidence of antituberculosis hepatotoxicity in thefirst 2 weeks of therapy was 7%, consisted of hepatitis (1 cases), mixed (2 cases), and asymptomatic (3 cases). There was no difference in sex as well as in nutritional state distribution found in cases with hepatotoxicity.